On One Sequence of Polynomials and the Radius of Convergence of Its Poisson–Abel Sum - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For one sequence of polynomials arising in the construction of the numerical-analytic method for finding periodic solutions of nonlinear differential equations, we determine the explicit form of the Poisson–Abel sum and the exact solution of the equation for finding the radius of convergence of this sum.